Pemantauan dan Pengendalian Manajemen Menggunakan Pendekatan Vale Engineering Sebaga Upaya Efisiensi Penggunaan Anggaran Perbaikan Sarana dan Prasarana di RSU Anna Medika Madura - Alfian , Mohammad Yusril; Susanti, Eny (Jurnal Ners, 2024)
Building maintenance is a planned maintenance activity or damage prevention maintenance. To ensure the continuity and quality of health services to the community, the hospital building and all equipment and supplies integrated within it must receive attention from the hospital management, especially in the aspect of regular and timely care and maintenance, in order to avoid more serious damage and requires high repair costs. The problem in this research is that repairs to facilities and infrastructure are not resolved quickly so that the damage becomes more extensive and subsequent repairs use a larger budget. The aim of this research is to analyze management monitoring and control using value engineering on the efficient use of the budget for improving facilities and infrastructure at RSU Anna Medika Madura. This research is analytical research with the research approach used is One-Group Pre-Post Test Design. The population in this research is the person in charge of facilities and infrastructure as well as the financial treasurer of RSU AMM. The sampling technique used was purposive sampling. The selection of subjects in this research used a purposive sampling method, namely that subjects were selected according to the data source sampling technique with certain considerations. After carrying out the Value Engineering analysis, the savings percentage was 28.12%. Based on the results above, the Value Engineering technique in improving monitoring and control of repair cost budgets has the power to be a process of saving repair cost budgets.